2011
DOI: 10.1203/pdr.0b013e31821be094
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Increases the Uniformity of Lung Aeration at Birth in Ventilated Preterm Rabbits

Abstract: Surfactant deficiency is a major cause of respiratory failure in newborns. We have investigated the roles of surfactant and positive end-expiratory pressure (PEEP) in the development of a functional residual capacity (FRC) and the distribution of ventilation at birth. Preterm rabbit pups (28 d GA) were delivered and received either saline or surfactant and then ventilated with (3PEEP) or without (0PEEP) 3 cm H 2 O PEEP (groups: saline/0PEEP, surfactant/ 0PEEP, saline/3PEEP, surfactant/3PEEP). Lung gas volumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 21 publications
3
39
1
Order By: Relevance
“…PC X-ray images of the lungs at FRC were analyzed to assess the uniformity of lung aeration using a phase retrieval analysis that calculates lung gas volumes from the images (27,37,38). PC X-ray images were divided into four quadrants, vertically down the spine and horizontally at the seventh rib.…”
Section: Methodsmentioning
confidence: 99%
“…PC X-ray images of the lungs at FRC were analyzed to assess the uniformity of lung aeration using a phase retrieval analysis that calculates lung gas volumes from the images (27,37,38). PC X-ray images were divided into four quadrants, vertically down the spine and horizontally at the seventh rib.…”
Section: Methodsmentioning
confidence: 99%
“…Surfactant also plays an important role in creating and maintaining FRC at birth, by reducing the surface tension, lung recoil and the transpulmonary pressure gradient for lung liquid moving back to the alveolar space [50,51]. In addition, surfactant greatly increases the uniformity of lung aeration, which indicates that surface tension determines whether the air/liquid interface progresses down both airways at each airway branch [51].…”
Section: Pulmonary Transitionmentioning
confidence: 99%
“…In addition, surfactant greatly increases the uniformity of lung aeration, which indicates that surface tension determines whether the air/liquid interface progresses down both airways at each airway branch [51]. …”
Section: Pulmonary Transitionmentioning
confidence: 99%
“…Siew et al [10] showed that PEEP greatly facilitates aeration of the distal airways and prevents distal airway collapse at end expiration in very preterm rabbits mechanically ventilated from birth. In a later study [11] the same group showed that PEEP and Curosurf ® had additive effects on functional residual capacity and that Curosurf markedly improved the uniformity of ventilation irrespective of whether or not PEEP was applied. These results are in agreement with our results using preterm rabbits.…”
Section: Surfactant Activitymentioning
confidence: 95%